Realization software of determination of functional profiles and level of guarantees of automated systems from an unauthorized access - Бучик, С. С.; Нетребко, Р. В. (Science-based technologies, 2017)
In the article basic stages of implementation of software of determination or concordance of level of guarantees of correctness of realization of functional services of safety phases in facilities of security of information of automated systems from an unauthorized access in Ukraine on the basis of undertaken by authors earlier theoretical studies of determination or concordance of level of guarantees are shown. Planning of work of the program is carried out by means of diagrams of Data Flow Diagram. More detailed flow-charts of work of software and algorithms are built. The prototype of software is realized and examples of work on each of basic blocks of work, that were preliminary projected in diagrams and flow-charts of algorithms are made. Certain advantages and drawbacks of the worked out software of functional profile of security and of level of guarantees are determined. The further steps of continuation of research in this direction are indicated.